BATANG FIELD RESERVOIR 3D MODELING AND VOLUMETRIC UNCERTAINTY ANALYSIS - Zainal Arifin, M.
3D reservoir modeling has been done to integrate geological, geophysical and petrophysical data which have been studied in Batang field. Modeling was done using geostatistical method. Model was validated in two ways, first by comparing statistic of model data versus well data. The second validation was done by excluding one well data on modeling process then comparing data model and the well data (blind test well method). The first validation method indicates that statistics of model data match with statistic of well data. The second validation indicates that the model is able to predict reservoir condition very well. In the well validation location, properties of model data and well data have correlation coefficient of 76% for porosity, 65% for Vsh and 95% for water saturation. 3D reservoir model was used for calculating volumetric original oil in place (OOIP). Since the quantity and quality of Batang reservoir data are not good, it is causing the uncertainty on volumetric OOIP. Design of experiment method was used to analyze uncertainties on volumetric OOIP. This method analyzes uncertainties on each variable which used for calculating volumetric OOIP. This method also gave regression equation which used to calculate probabilistic volumetric OOIP. Calculation of probabilistic OOIP was done using the regression equation and Monte Carlo simulation method. This method is able to accommodate uncertainties on each variable which used for calculating OOIP.